Healing Delay in Venous Leg Ulcer Post Endovenous Laser Ablation: A Single Center Study (Bangladesh Medical Journal, 2026)
Venous leg ulcer (VLU) is the most advanced manifestation of chronic venous insufficiency and remains a major cause of morbidity, prolonged disability, and healthcare burden worldwide. Although endovenous laser ablation (EVLA) improves ulcer healing by correcting superficial venous reflux, delayed healing remains common in a subset of patients. This study aimed to evaluate factors associated with delayed healing of VLUs following EVLA. This retrospective cohort study was conducted at the Department of Vascular Surgery, Ibrahim Cardiac Hospital & Research Institute, Dhaka, Bangladesh, from January 2020 to December 2024. A total of 256 adult patients with duplex-confirmed venous leg ulcers who underwent EVLA with or without adjunctive foam sclerotherapy were included using consecutive sampling. Delayed healing was defined as failure of complete epithelialization or a